1996
DOI: 10.1021/bi9516440
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the p68/p58 Heterodimer of Human Immunodeficiency Virus Type 2 Reverse Transcriptase

Abstract: Recently we demonstrated that the p58 subunit of p68/p58 HIV-2 reverse transcriptase (RT) heterodimer, produced by processing of p68/p68 homodimer with recombinant HIV-2 protease, terminates at Met484 [Fan, N., et al. (1995) J. Biol. Chem. 270, 13573-13579]. Here we describe purification and characterization of the p68/p58 heterodimer of recombinant HIV-2 RT. It exhibited both RT and RNase H activities, obeyed Michaelis-Menten kinetics, and was competitively inhibited by the DNA chain terminator ddTTP (Ki[app]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
15
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 26 publications
4
15
0
Order By: Relevance
“…In each of our model assays, we found relatively small quantitative differences between HIV-1 and HIV-2 RNase H activities under standard assay conditions, in agreement with Fan et al (16). However, with lower enzyme concentrations, we observed that HIV-2 RT is compromised in its ability to catalyze total RNase H cleavage (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In each of our model assays, we found relatively small quantitative differences between HIV-1 and HIV-2 RNase H activities under standard assay conditions, in agreement with Fan et al (16). However, with lower enzyme concentrations, we observed that HIV-2 RT is compromised in its ability to catalyze total RNase H cleavage (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…In earlier work (16,28,29,61), the DNA polymerase activity of HIV-2 RT was found to be similar to that of HIV-1 RT. The results for RNA-dependent synthesis of minus-strand DNA with an RT/primer-template ratio of 1 showed no difference in HIV-1 and HIV-2 RT activities, in agreement with these previous studies; however, when this ratio was reduced to 0.1, HIV-1 RT exhibited a higher rate and greater extent of DNA synthesis (almost 3-fold and ϳ2-fold, respectively) than the HIV-2 enzyme (Fig.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…RT from 98CN009 was the least efficient enzyme in the panel for all three activities. Consistent with previous reports (14,27,49,56), the DNA polymerase and RNase H activities of RT from the HIV-2 strain EHO-287 were significantly less than those of most of the HIV-1 RTs.…”
Section: Methodssupporting
confidence: 92%
“…(Pan troglodytes troglodytes) and the 89% amino acid identity between RTs from HIV-2 group A and sooty mangabey SIV illustrate the more proximal relationships between the two HIV types and the SIV taxa from which they originated. The HIV-1 enzymes are, in general, slightly more active than their HIV-2 counterparts (14,27,49,56), which has been proposed to contribute to the greater virulence of the HIV-1 strains than of the HIV-2 strains (19,44). Many of the same factors that drive rapid viral evolution and diversification of the M group (7,8,17,40,43) have also contributed to the rapid appearance of drug resistance mutations in the RT and protease (PR) genes.…”
mentioning
confidence: 99%